2021
DOI: 10.5430/ijfr.v12n3p261
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion in Zimbabwe: Determinants, Challenges, and Opportunities

Abstract: Financial inclusion is a highly topical issue for policymakers since inclusive finance is viewed as a channel of social and economic development. Therefore, this paper seeks to ascertain and examine the determinants, challenges, and opportunities for financial inclusion in Zimbabwe. The research is done by examining existing literature and estimating Logit and Probit models. This paper finds that, the major determinants of financial inclusion in Zimbabwe are; gender, age, education, income levels, employment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…While, other researchers such as Allen et al (2014), Beck et al (2006), Mbutor and Uba (2013), Singh (2016), Olaniyi (2017) and IJOEM 18,7 Abimbola et al (2018) have all demonstrated that financial inclusion can reduce inequality, poverty levels and increase private sector investment. But, other scholars including Mohan (2006), Agarwal (2010), Cnaan et al (2012) and Shatrma and Kukreja (2013) believe that financial inclusion influences the development of the economy. In Pakistan, many studies have been done by Fayaz et al (2006), Bashir and Mehmood (2010), Ahmad et al (2015), Chandio et al (2017Chandio et al ( , 2018, and Ashfaq and Jan (2019) to see the impact of formal credit on major crops (wheat, rice, maize and sugarcane) productivity.…”
Section: Introductionmentioning
confidence: 99%
“…While, other researchers such as Allen et al (2014), Beck et al (2006), Mbutor and Uba (2013), Singh (2016), Olaniyi (2017) and IJOEM 18,7 Abimbola et al (2018) have all demonstrated that financial inclusion can reduce inequality, poverty levels and increase private sector investment. But, other scholars including Mohan (2006), Agarwal (2010), Cnaan et al (2012) and Shatrma and Kukreja (2013) believe that financial inclusion influences the development of the economy. In Pakistan, many studies have been done by Fayaz et al (2006), Bashir and Mehmood (2010), Ahmad et al (2015), Chandio et al (2017Chandio et al ( , 2018, and Ashfaq and Jan (2019) to see the impact of formal credit on major crops (wheat, rice, maize and sugarcane) productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The stark reality is that in 2014, 23% of the Zimbabwean adult population was deemed financially excluded . Although this is a significant improvement from the 40% statistic in 2011, there is still much room for improvement, considering that in 2017, approximately 67% were financially excluded (Masiyandima et al, 2017;Barugahara, 2021;. Prior research (Barugahara, 2021;Library of Congress, 2021), suggests that financial inclusion is hindered by the following factors:…”
Section: Financial Inclusion Challenges In Zimbabwementioning
confidence: 99%
“…The concept of "financial inclusion" speaks to the equitable and affordable access, of individuals, to financial services (Barugahara, 2021;. Such financial services can include access to bank account, access to formal investment options, and access to formal borrowing options (Chitokwido et al, 2014).…”
Section: Financial Inclusion Challenges In Zimbabwementioning
confidence: 99%
See 1 more Smart Citation
“…Considering a very low penetration of banking services among the rural and vulnerable population, the banking regulator body of the country, i.e. the Reserve Bank of India (RBI), has introduced a number of banking reforms to enhance the coverage of banking services to the remotest place of the country (Aggarwal, 2014). The Pradhan Mantri Jan Dhan Yojna (PMJDY) was launched by the government in the year 2014 for the universalisation of formal financial services at affordable costs through technological innovations and to help a larger population to come out of the trap of poverty (Yadav et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%